KECERNAAN ENERGI, PROTEIN, DAN MINERAL KALSIUM DAN FOSFOR KUDA PACU MINAHASA YANG DIBERI PAKAN LOKAL DAN IMPOR - Mende, Inggrit Shinta; Tulung, Y. L.R.; Umboh, J. F.; Kaunang, W. B. (Universitas Sam Ratulangi, 2015)
ABSTRACT ENERGY, PROTEIN, AND MINERAL CALCIUM AND PHOSPHORUS DIGESTIBILITY OF RACE HORSES CONSUMED LOCAL AND IMPORTED FEEDSTUFFS. An experiment was conducted to determine the ability of race horse in digesting either local or imported feedstuffs used mostly by race horse owner in Minahasa. The digestibility of nutrients is a determinant factor in feedstuffs or diet quality consumed by horses.Â Therefore, a study on determining the digestibility of feedstuffs is really needed because the rate of digestibility can be used as an indicator of how much nutrients in feedstuffs can be digested in the gastrointestinal tract. The present study was conducted using survey method.Â Data was collected using interview and direct observation on the race horses farmerâ€™s location. Data collected was: type and amount of diets (forage and concentrate) given to the horses, and amount of faeces (g.head-1.day-1), and 30 samples, 15 horses each using local feedstuffs, and 15 samples (horses) using imported feedstuffs. Data was statistically analyzed using t test. Research results showed that energy, protein, calcium, and phosphorus digestibility of imported feedstuffs significantly higher (P < 0,05) than local feedstuffs. It can be concluded that digestibility of imported feedstuffs is still better than local feedstuffs. Keywords: Digestibility, Energy, Protein, Calcium (Ca), Phosphorus (P), Race Horses, Imported Feedstuffs, Local Feedstuffs.